Puborectalis muscle and External Anal Sphincter: a functional unit? - Andromanakos, Nikolaos; Filippou, Dimitrios; Karandreas, Nikolaos; Kostakis, Alkiviadis (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Andromanakos N, Filippou D, Karandreas N, Kostakis A. Puborectalis muscle and External Anal Sphincter: a functional unit? Turk J Gastroenterol 2020; 31(4): 342-3.